Pengaruh Penggunaan Media Sosial Terhadap Perubahan Perilaku Berbahasa pada Remaja di Kota Surabaya - K. Salsabila, Allayna; P. E. Br Tampubolon, Dwi; T. Ayudiya, Mutiara; P. Sari, Fifin; F. Rahman, Alvero (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the influence of social media usage, particularly TikTok, on the linguistic behavior changes among teenagers in Surabaya. Using a qualitative approach, this research observes the language behavior of teenage content creators on TikTok and the impact of slang usage on their daily lives. The findings indicate that TikTok slang has positive effects, such as fostering creativity and group identity. However, it also presents negative impacts, including a decline in the quality of standard Indonesian, misunderstandings, and adverse effects on learning. This study provides insights for educators, parents, and related stakeholders to understand this phenomenon and develop more effective communication strategies.